Perancangan Buku Ilustrasi Sebagai Media Informasi Tentang Stres - Randa Januario Pratama; I Nyoman Miyarta Yasa (Universitas Bumigora, 2020)
Mental health has become a big problem in Indonesia. Adolescents are a category that is prone to stress, and is often handled inappropriately by themselves, relatives, or parents. Stress is still considered a trivial matter for most Indonesians. In fact, stress is one of the triggers for various kinds of physical and psychological ailments. The lack of interesting reading for teenagers about stress makes this phenomenon still difficult to get the first treatment before it continues to an undesirable stage. The purpose of this design is to create an illustrated book that discusses stress information with the content as simple as possible and attractive so that it is easily understood by adolescents. This design uses themethod design thinking in order to get the right problem-solving solution in designing the work. There are two media in the design, namely primary media, illustrated books, information about stress and secondary media, namely x-banners and merchandise. By designing this illustration book, it is hoped that it can become a new media choice as informative reading about stress.